Selective preemption strategies for parallel job scheduling. (11th November 2005) - Kettimuthu, Rajkumar; Subramani, Vijay; Srinivasan, Srividya; Gopalsamy, Thiagaraja; Panda, D.K.; Sadayappan, P.
Although theoretical results have been established regarding the utility of preemptive scheduling in reducing average job turnaround time, job suspension/restart is not much used in practice at supercomputer centres for parallel job scheduling. A number of questions remain unanswered regarding the practical utility of preemptive scheduling. We explore this issue through a simulation based study, using real job logs from supercomputer centres. We develop a tuneable selective suspension strategy and demonstrate its effectiveness. We also present new insights into the effect of preemptive scheduling on different job classes and deal with the impact of suspensions on worst case response time. Further, we analyse the performance of the proposed schemes under different load conditions.